Analisis Evaluasi Kinerja Portofolio Saham dengan Metode Sharpe pada Perusahaan Farmasi - Sofyan Marwansyah; Rani Kurniasari; Teni Agustina; Nurlaela Eva Puji Lestari (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to evaluate the performance of stock portfolios in the pharmaceutical sector listed on the Indonesia Stock Exchange using the Sharpe method. The performance assessment was conducted on seven pharmaceutical companies actively traded from January to December 2020. The data used includes monthly closing stock prices and the Bank Indonesia Certificate (SBI) interest rate as a proxy for the risk-free rate. The results show that PT Indofarma (INAF) had the highest Sharpe ratio of 0.3928, indicating the most optimal return relative to the risk taken. On the other hand, PT Kimia Farma (KAEF) recorded a negative Sharpe ratio, reflecting underperformance during the study period. These findings can serve as a reference for investors in making investment decisions in the pharmaceutical sector.